Product involutions with 0 or 1-dimensional fixed point sets on orientable handlebodies - Roger B. Nelson (International Journal of Mathematics and Mathematical Sciences)
Let h be an involution with a 0 or 1-dimensional fixed point set on an orientable handlebody M. We show that obvious necessary conditions for fibering M as A×I so that h=τ×r with τ an involution of A and r reflection about the midpoint of I also turn out to be sufficient. We also show that such a product involution is determined by its fixed point set.